2017
DOI: 10.17765/1983-1870.2016v9n3p507-515
|View full text |Cite
|
Sign up to set email alerts
|

Análise do desempenho motor e maturidade cognitiva de pré-escolares de Maringá (PR)

Abstract: Objetivou-se analisar o desempenho motor e a maturidade cognitiva de pré-escolares de Maringá (PR) em função da idade. Participaram 89 crianças com 04 e 05 anos, matriculados regularmente em Centros de Educação infantil (CMEI) do município de Maringá (PR). Os instrumentos foram a Bateria de Avaliação do Movimento para Crianças (MABC-2) e a Escala de Maturidade Mental Colúmbia. Para análise dos dados foram utilizados os testes de Friedman, “U” de Mann Whitney e coeficiente de correlação de Spearman, adotando-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…A similar result was obtained when Raven scores of children with different levels of motor performance were analyzed, that is, children without motor deficits had higher cognitive levels than those with severe motor deficits and low manual dexterity (Table 3). Supporting the association between motor performance and cognition and as in the study by Rocha et al (2016) with Brazilian preschool children, a very low but significant correlation was found between Raven and MABC-2 scores in children without DCD (Table 4).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A similar result was obtained when Raven scores of children with different levels of motor performance were analyzed, that is, children without motor deficits had higher cognitive levels than those with severe motor deficits and low manual dexterity (Table 3). Supporting the association between motor performance and cognition and as in the study by Rocha et al (2016) with Brazilian preschool children, a very low but significant correlation was found between Raven and MABC-2 scores in children without DCD (Table 4).…”
Section: Discussionsupporting
confidence: 65%
“…In Brazil, only one study on the relationship between cognition and coordination disorder was found. Rocha et al (2016) investigated the relationship between motor performance, cognitive maturity, and age in 89 children aged 4 and 5 years old of the municipal education network in the city of Maringá (PR). The children had higher mean cognitive maturity and, although a significant low correlation (r = 0.22) between cognition and performance in the MABC-2 test was found, there was no relationship between a possible DCD diagnosis and cognitive maturity.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Rocha et al (2016) found a correlation impairment of cognitive development of children with DCD when compared to children with typical development (Rocha et al, 2016). Although Silva et al (2012) found no significant relationship between learning disabilities and motor problems (with a sample size of only 19 children), there was significant comorbidity with ADHD (41.2% of children with DCD) in the study by Cardoso et al (2014).…”
Section: Discussionmentioning
confidence: 74%
“…Da Rocha et al [16] avaliaram 89 crianças pré-escolares de ambos os sexos com idade de 4 a 5 anos através da Escala de Maturidade Mental Colúmbia (EMMC), essa fornece uma aproximação da capacidade cognitiva de indivíduos de 3 anos e 6 meses a 9 anos e 11meses de forma especifica, a maioria (50,60%) das crianças de quatro anos (46,7%) e cinco anos (54,5%) apresentou classificação médio superior para maturidade cognitiva, sendo que, do total, apenas uma criança de quatro anos apresentou classificação inferior. Diante dos resultados puderam observar uma boa estimulação nesta área.…”
Section: Discussionunclassified